2020
DOI: 10.1002/jmv.26695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renin‐angiotensin‐aldosterone system inhibitors on disease severity and mortality in patients with COVID‐19: A meta‐analysis

Abstract: To investigate the effects of renin‐angiotensin‐aldosterone system (RAAS) inhibitors on the prognosis in patients with coronavirus disease 2019 (COVID‐19). A meta‐analysis was performed. We systematically searched PubMed, the Cochrane Library, the Web of Science, EMBASE, medRxiv, and bioRxiv database through October 30, 2020. The primary and secondary outcomes were mortality and severe COVID‐19, respectively. We included 25 studies with 22,734 COVID‐19 patients, and we compared the outcomes between patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 50 publications
1
39
0
1
Order By: Relevance
“…This hypothesis was supported by initial findings that these medications were more frequently used in COVID-19 patients with cardiac injury or in those with severe form of disease ( 8 , 9 ). Nevertheless, later reports failed to show any negative relationship between adverse outcome and use of ACEI and ARB in COVID-19 patients ( 10 13 ).…”
Section: Antihypertensive Therapy In Covid-19mentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis was supported by initial findings that these medications were more frequently used in COVID-19 patients with cardiac injury or in those with severe form of disease ( 8 , 9 ). Nevertheless, later reports failed to show any negative relationship between adverse outcome and use of ACEI and ARB in COVID-19 patients ( 10 13 ).…”
Section: Antihypertensive Therapy In Covid-19mentioning
confidence: 97%
“…There was a long discussion regarding the impact of antihypertensive therapy in COVID-19 patients and particularly of angiotensin-converting enzyme inhibitors (ACEI) and blockers of angiotensin I receptors (ARB). After initial reports that showed higher prevalence of use of these medications in COVID-19 patients with cardiac injury and more severe course of disease ( 8 , 9 ), numerous original studies and meta-analysis reported no relationship with severity or mortality in COVID-19 patients ( 10 , 11 ) or even benefit of taking renin-angiotensin-aldosterone inhibitors in COVID-19 patients ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that ACEi/ARB therapy does not influence negatively mortality or susceptibility to virus infection [ 73 , 74 , 75 , 76 , 77 ]. Furthermore, evidence of ACEi/ARB effectiveness is reported in publications based on meta-analysis as well [ 78 , 79 ]. The recent BRACE-CORONA trial suggests that treatment interruption does not positively affect the survival of COVID-19 patients, thus ACEi/ARB therapy should be continued [ 80 ].…”
Section: Is Acei/arb Therapy During Sars-cov-2 Infection Safe?mentioning
confidence: 99%
“…The first outbreak of this new disease originally took place in the city of Wuhan (China), rapidly spreading in the southeast of Asia and, recently, in other continents like Europe, North America and Africa 1 . The astonishing rate at which COVID is expanding compared to previous coronavirus related diseases (SARS-CoV and MERS-CoV), in conjunction with the absence of approved drugs or effective therapeutic approaches for its treatment, has gathered the attention of the international community, which is promoting a cooperative effort to face this emergency 3 , 4 . On January 2020 indeed, the International Health Regulations Emergency Committee of the World Health Organization declared the outbreak a “public health emergency of international concern” in responding to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, however, a great effort involves the targeting of non-structural viral proteins which are instead essential for the viral replication and the maturation processes, thus representing a crucial and specific target for anti-COVID drug development 3 , 10 . In this regard, the crystallographic structure of the SARS-CoV-2 main protease (M pro ), also known as C30 Endopeptidase, was elucidated and made available to the scientific community with impressive timing, just a few weeks after the first COVID-19 outbreak (PDB ID: 6LU7).…”
Section: Introductionmentioning
confidence: 99%